Femtosecond Laser Ablation Reveals Antagonistic Sensory and Neuroendocrine Signaling that Underlie C. elegans Behavior and Development - Samuel H. Chung (Cell Reports, 2013)
The specific roles of neuronal subcellular components in behavior and development remain largely unknown, even though advances in molecular biology and conventional whole-cell laser ablation have greatly accelerated the identification of contributors at the molecular and cellular levels. We systematically applied femtosecond laser ablation, which has submicrometer resolution in vivo, to dissect the cell bodies, dendrites, or axons of a sensory neuron (ASJ) in Caenorhabditis elegans to determine their roles in modulating locomotion and the developmental decisions for dauer, a facultative, stress-resistant life stage. Our results indicate that the cell body sends out axonally mediated and hormonal signals in order to mediate these functions. Furthermore, our results suggest that antagonistic sensory dendritic signals primarily drive and switch polarity between the decisions to enter and exit dauer. Thus, the improved resolution of femtosecond laser ablation reveals a rich complexity of neuronal signaling at the subcellular level, including multiple neurite and hormonally mediated pathways dependent on life stage.